A Study of Pressure Surge Effects on Transportation Pipeline - Muhammad Fahmi Bin Mustafa, Muhammad Fahmi (Universiti Teknologi Petronas, 2008)
This report basically discusses the research that has been done and fundamental understanding of the chosen topic, which is a study of pressure surge effects on transportation pipelines. In this report the author required to study what is pressure surge since pressure surge are one of the problems occurred in the pipeline system and several cases reported that there were pipe burst and pipe support collapse due to pressure surge. The objectives from this project basically are to know what pressure surge is, how pressure surge occurred in the pipeline, and what the causes for pressure surge to occur. This report was prepared based on the author findings and simulation that has been done in order to show how pressure surge will occur and effect to the pipeline. During this project, the scope of study mainly consists of 3 parts. First part is to know how pressure surge will occur in pipeline based from the research and literature review of what other authors said regarding this problems. The second part is to develop a pressure surge system by using spreadsheet in order to show how surge will happen. The last part is to calculate pressure surge that will occurred from spreadsheet by using data given. In the report, the author also included the progress of the pressure surge research. Also author had included steps taken from beginning to the completion of the project and using data given by TNB from one of their hydro plant in order to show pressure surge effect. The result from this project is that time of valve closure has relationship to the pressure surge and also method to minimize pressure surge by using surge tank.